1988
DOI: 10.1136/hrt.59.5.588
|View full text |Cite
|
Sign up to set email alerts
|

Coronary angioplasty in pregnancy.

Abstract: SUMMARY Myocardial infarction is rare in pregnancy. A 30 year old white primigravida had an anterior infarct at 20 weeks' gestation, which was followed by troublesome angina. Coronary angiography showed a tight stenosis of the left anterior descending coronary artery. This was treated successfully by percutaneous transluminal coronary angioplasty.Case report A 30 year old white woman presented at 20 weeks' gestation in her first pregnancy with paraesthesiae and severe pain in her left arm and hand. This was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 17 publications
0
20
0
3
Order By: Relevance
“…Even though AMI during pregnancy is an indication for PTCA, experience is limited due to the rarity of AMI during pregnancy and the limited availability of coronary intervention for AMI worldwide. To date there are only nine reports of coronary interventions during pregnancy [4][5][6][7]11,[13][14][15][16]. Four of these were primary procedures for management of AMI [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Even though AMI during pregnancy is an indication for PTCA, experience is limited due to the rarity of AMI during pregnancy and the limited availability of coronary intervention for AMI worldwide. To date there are only nine reports of coronary interventions during pregnancy [4][5][6][7]11,[13][14][15][16]. Four of these were primary procedures for management of AMI [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The salient features of the present case could be as follow: 1) Acute myocardial infarction in pregnancy is a very rare occurrence [1]; the present case is one of the very few cases reported from India so far; 2) The patient presented with acute onset of myocardial infarction during the second trimester, while majority of reported cases have depicted that pregnancy-related myocardial infarction is more common during the third-trimester [7]; 3) The symptom-to-door time in our patients was only 20 minutes; 4) our patient lacked conventional coronary risk factors [3] including gestational diabetes or eclampsia, except a family history of coronary artery disease; 5) While the most common cause for pregnancy-related acute myocardial infarction remains atherosclerosis or coronary dissection [7], our case displayed a distinct profile; and 6) An association of acute cerebrovascular event in the post-partum period post-primary PCI has not been reported so far.…”
Section: Discussionmentioning
confidence: 97%
“…The prognosis is often poor as high maternal mortality and fetal loss is frequently associated with pregnancy-related myocardial infarction [2]. Back in 1988, Cowan et al reported the first case of percutaneous coronary intervention (PCI) during pregnancy in a 30-year-old woman with myocardial infarction [3]. Since then, numerous cases of coronary angioplasty during pregnancy have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive literature search revealed only 5 cases of PTCA performed during pregnancy [7,9,19,20,26]. Our patient differed from these patients in several respects: she had no risk factors except for a smoking history discontinued prior to pregnancy, the culprit vessel was the LAD and it was totally occluded, there was evidence of additional thrombus in a significant branch of that vessel, and her cardiac recovery was potentially threatened with the need for an emergency cesarean section less than 2 wk after her infarct.…”
Section: Discussionmentioning
confidence: 99%